Social Well-Being of Teenage Social Media Users in Gelam Village: Kesejahteraan Sosial Pengguna Media Sosial Remaja di Desa Gelam - Islami , Mega Wahyu; Maryam, Effy (Universitas Muhammadiyah Sidoarjo, 2025)
Background: The rapid development of technology has changed how teenagers communicate, with social media becoming their primary platform. Specific Background: This shift has raised concerns regarding teenagers’ social well-being, including miscommunication and reduced empathy during online interactions. Gap: Few studies have specifically mapped the level of social well-being among adolescent social media users in local communities. Aim: This study aimed to describe the social well-being of teenagers who actively use social media in Gelam Village, Sidoarjo. Method: A quantitative descriptive approach was employed, involving 214 respondents selected through purposive sampling. Data were collected using a social well-being Likert scale and analyzed using descriptive statistics with SPSS 25. Results: Findings revealed that 72.6% of respondents were in the medium social well-being category, with balanced results across gender. Novelty: This study provides localized empirical evidence of teenagers’ social well-being levels. Implications: The results can guide parents, educators, and policymakers in designing programs to strengthen teenagers’ positive social interactions both online and offline. Highlights: Most teenagers’ social well-being is in the medium category Social well-being is consistent across gender Social media plays a role in shaping social integration Keyword: Social Well-Being, Teenagers, Social Media, Descriptive Study, Mental Health